The Outcomes on Mother and Child in Teenage Pregnancies - Sadaf Ijaz, Saadia Hassan, Kiran Khan, Falik Naz, Ayesha Samad Dogar, Nargis Gulab, Bibi Sajida, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The goal of this research is to identify the risks to mother and child health when pregnant teenagers are adolescent. Methods: 94 patients participated in this study. Patients were aged 14–40 years. Patients' demographics were recorded following written consent. The frequency of pre-eclampsia, gestational diabetes, and postpartum hemorrhage was determined. Both groups were compared for adverse outcomes (cesarean section, instrumental delivery, induction and prolongation of labor, hypertension). NICU admission, low birth weight, low Apgar score, and mortality were observed. Results: In fetal outcomes, we found higher frequency of perinatal mortality, low birth weight and NICU admission in teen age pregnancy as compared to other group with p value <0.005. In maternal outcomes, frequency of anemia, pre-eclamspa, a post-partum hemorrhage and gestational diabetes were higher among cases of teenage pregnancy. Conclusion: This study found that low birth weight, delayed intrauterine development, and premature neonatal critical care admission are rising. Teen pregnancy increases the risk of anemia, UTI, high blood pressure, and surgery. Keywords: Post-Partum haemorrhage, Maternal outcome, Pre-eclampsia, Fetal outcome.